Anthroponotic Cutaneous Leishmaniasis in Nonendemic Quarters of a Centeral City in Iran - AR Zahraei-Ramazani; MR Yaghoobi-Ershadi; AR Mokhtari; AA Akhavan; H Abdoli; MH Arandian (Tehran University of Medical Sciences, 2007)
Bacground: The aim of this study was to determine the status of the cutaneous leishmaniasis in some nonendemic quarters in the city of Isfahan, Isfahan Province, central Iran. Methods: A total of 16380 primary school students aged 6-17 years old and a total population of 2892 persons in 700 households in four nonendemic quarters were questioned and examined for the presence of ulcer or scar. Sand flies were collected using sticky paper traps. Results: A rate of 4.18% for scars and 0.3% for active lesions in the primary school children were showed. The households showed a prevalence of 11.3% for scars and 0.5% for ulcers. Two thousand and seventy four sand flies were collected and 10 species were identified. The most common sand fly species in indoor and outdoor resting places was P.sergenti. Conlusion: The present investigation revealed that Anthroponotic Cutaneous Leishmaniasis is in an epidemic status in these quarters. Human is considered the main reservoir and transmission is believed to be from human to human by P.sergenti.